First report in Venezuela of Blastocystis sp and Entamoeba coli in Pelecanus occidentalis of Coche Island, Venezuela (Boletin Médico de Postgrado, 2022)
In Venezuela, and particularly on the paradisiacal island of Coche, there are no studies on the pelican (Pelecanus occidentalis) as an agent of zoonotic transmission of enteroparasites (chromists, amoebae, helminths) or as their reservoir (Anisakis sp). For this reason, a descriptive cross-sectional study was carried out, with an accidental sample, to determine the presence of intestinal parasites in these seabirds, analyzing 100 samples of fresh feces obtained in two resting places where only this species usually rests. The samples were analyzed on the same day using the saline and lugol's techniques. An intestinal parasitosis frequency of 60% of the analyzed samples was determined, finding the enteroparasites Ascaridia spp. (50%), Blastocystis sp. (10%), Isospora spp. (10%), Entamoeba coli (10%), Raillietina spp. (10%), Trichomonadida (5%) and Capillaria spp. (5%). Due to the presence of parasites with medical/zoonotic potential, 30 human patients with gastrointestinal symptoms were evaluated coprologically to detect the diversity and frequency of human parasites that circulate in patients on the island, finding mostly Blastocystis sp (80%) and Entamoeba coli (10%). This is the first national report of pelican enteroparasites, where taxa of zoonotic importance are described.
Keywords: birds; guano australis; parasites; zoonosis; Venezuela